Exploring Undergraduate Students’ Online Interaction in Academic Reading Classroom via WhatsApp Application - Ida Yulianawati; Natalia Anggrarini; Anes Nurul Bahari (Yayasan Karinosseff Muda Indonesia, 2021)
This research aimed to discuss the potential of the WhatsApp application as a tool of online learning at a higher educational level that could stimulate students’ interactions and discussion with the lecturer or their peers. With interactions, they can experience and develop an awareness of behaviors required to facilitate their participation in online learning. Therefore, this study identified the specific and general types of undergraduate students’ online interactions and investigated their patterns across time. The study was carried out by 6 undergraduate students of the 2019/2020 academic year in the English Education Department, Wiralodra University. Students’ posts in WhatsApp group discussion were analyzed in terms of online interaction types identified by MacKinnon (2000) and Jung et al. (2002). The result shows that the students mostly expressed their opinions and judgments in academic-related discussions rather than moved to a higher level of knowledge construction, such as providing their own example upon their ideas and elaborating more on certain topics in the discussion. Further investigation can be done to find the factors that affect students’ interaction, the relationship between topics, and online interactions in another online learning platform.